Starting structures and NMR and simulation relaxation data for the structural ensembles of Dengue protease NS2B/NS3pro - Agback, Peter; Agback, Tatiana; Lesovoy, Dmitry; Han, Xiao; Lomzov, Alexander; Sun, Renhua; Sandalova, Tatyana; Orekhov, Vladislav; Achour, Adnane (Swedish University of Agricultural Sciences, 2023)
The dengue protease NS2B/NS3pro has been reported to adopt either an ‘open’ or a ‘closed’ conformation. We have developed a conformational filter that combines nuclear magnetic resonance (NMR) with molecular dynamics (MD) simulations to identify conformational ensembles that dominate in solution. Experimental values derived from relaxation parameters for the backbone and methyl side chains were compared with the corresponding back-calculated relaxation parameters of different conformational ensembles obtained from free MD simulations. Our results demonstrate a high prevalence for the ‘closed’ conformational ensemble while the ‘open’ conformation is absent, indicating that the latter conformation is most probably due to crystal contacts. Conversely, conformational ensembles in which the positioning of the co-factor NS2B results in a ‘partially’ open conformation, previously described in both MD simulations and X-ray studies, were identified by our conformational filter. Altogether, we believe that our approach allows for unambiguous identification of true conformational ensembles, an essential step for reliable drug discovery.

Dengueproteaset NS2B/NS3pro har rapporterats anta antingen en "öppen" eller en "stängd" konformation. Vi har utvecklat ett konformationsfilter som kombinerar kärnmagnetisk resonans (NMR) med molekylär dynamiska (MD)-simuleringar för att identifiera konformationella ensembler som dominerar i lösning. Experimentella värden härledda från relaxationsparametrar för ryggraden och metylsidokedjorna jämfördes med motsvarande beräknade relaxationsparametrar för olika konformationella ensembler erhållna från fria MD-simuleringar. Våra resultat visar en hög prevalens för den "slutna" konformationsensemblen medan den "öppna" konformationen är frånvarande, vilket indikerar att den senare konformationen troligen beror på kristallkontakter. Omvänt identifierades konformationella ensembler där positioneringen av kofaktorn NS2B resulterar i en "delvis" öppen konformation, som tidigare beskrivits i både MD-simuleringar och röntgenstudier, av vårt konformationsfilter. Sammantaget tror vi att vårt tillvägagångssätt möjliggör entydig identifiering av verkliga konformationella ensembler, ett viktigt steg för tillförlitlig läkemedelsupptäckt.
Startstrukturer och NMR- och simuleringsrelaxationsdata för de strukturella ensemblerna av Dengue-proteas NS2B/NS3pro
Keywords: NMR spectroscopy; NMR-spektroskopi; molecular dynamics; molekyldynamik; nuclear magnetic resonance; Dengue 2 virus; Dengue 2 virus; NMR; NMR; backbone dynamics; proteiners ryggradsdynamik; MD; MD; MD calculations of relaxation parameters; MD beräkningar av relaxationsparametrar; Dengue virus; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi); Other Physics Topics; Annan fysik; Structural Biology; Strukturbiologi